2017
DOI: 10.15242/ijacebs.a0217017
|View full text |Cite
|
Sign up to set email alerts
|

Column Studies on Chromium (VI) Adsorption onto Kala Jamun (Syzygiumcumini L.) Seed Powder (KSP)

Abstract: Abstract-This paper evaluate the industrial use of Kala Jamun (Syzygiumcumini L.) Seed powder (KSP) for the continuous adsorption of Cr(VI) in a column adsorption process. Adsrption of Cr(VI) onto Kala jamun Seed Powder have been examined with the variation of (a) bed depth of the adsorbents, (b) flow rate of the adsorbents and (c) Cr(VI) concentration. The results showed that both the adsorption and the regeneration of the Cr(VI) onto Kala Jamun (Syzygiumcumini L.) seed Powder (KSP) can effectively occur in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The kinetics of adsorption is studied using various models including the Thomas model (TM) and Yoon-Nelson (YN) model. The results of breakthrough curves were compared with other agricultural waste used for the removal of Pb (II) and were in agreement with the reported results [ 46 , 47 ]. Overall results showed that the column studies explain better performance in the removal of Pb (II) at lower flow rates.…”
Section: Resultssupporting
confidence: 86%
“…The kinetics of adsorption is studied using various models including the Thomas model (TM) and Yoon-Nelson (YN) model. The results of breakthrough curves were compared with other agricultural waste used for the removal of Pb (II) and were in agreement with the reported results [ 46 , 47 ]. Overall results showed that the column studies explain better performance in the removal of Pb (II) at lower flow rates.…”
Section: Resultssupporting
confidence: 86%